Musikalisches Zitat als kulturelle Assoziation. Die ästhetische Bedeutung des musikalischen Zitats in der koreanischen Musik des 20. und 21. Jahrhunderts - Hee Sook Oh (Zeitschrift der Gesellschaft für Musiktheorie, 2012)
Musical quotation, as a technique of using the pre-existing materials in the music composition, has an important significance in both quantitative and qualitative aspects since the late 20th century, as can be seen from works of Bernd Alois Zimmermann, Luciano Berio, Mauricio Kagel, Alfred Schnittke, George Rochberg, George Crumb. In terms of aesthetics, the musical quotation is closely related with postmodernism as the technique deviates from the aesthetics of originality and reveals musical diversity. In this respect, it can be said that ›musical quotation‹ is an important keyword which describes the late 20th century.